The prevalence of current water pipe use among Iranian male population: a systematic review and meta-analysis - Nematollahi, Shahrzad; Hosseini, Jalil; Abduli, Mitra; Sheikh-Milani, Arezoo; Feizi, Shahoo; Abbasi-Fashami, Mahta (Archives of Men’s Health, 2020)
Introduction: Waterpipe as a traditional method of tobacco consumption is a public health challenge. Considering the growing trend of waterpipe (hookah) use in Iran, this systematic review aimed to measure the pooled prevalence of waterpipe current use among Iranian men. Materials and Methods: The present systematic review was conducted on the published cross-sectional studies during 2009-2019 aiming at estimating the prevalence of waterpipe current use among Iranian men. Current use of waterpipe was defined as using waterpipe within the preceding 30 days. Random Effect model was used to estimate the pooled prevalence by STATA v.14. Results: Ten cross-sectional epidemiologic studies with a total sample size of of 6,263 were included in the meta-analysis. The pooled prevalence of waterpipe current use among Iranian men was estimated at 25% (95% Confidence Interval: 30-20%). Conclusions: There are a variety of definitions for current use of waterpipe across studies. The results of this study suggest a high prevalence of current use of waterpipe among Iranian men during 2009-2019. Increased use of waterpipe in communities should be considered as a public health concern and a matter of priority by health policymakers. Preventive programs should take into account the acceptability and appealing nature of waterpipe among Iranian population and consider them as important modifiable factors.